Usulan Perbaikan Proses Produksi CV Stadium Sport Banjarnegara Menggunakan Lean Manufacturing - Egi Yostama; Anisa Kharismawati (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. CV Stadium Sport Banjarnegara is a garment manufacturing company producing jersey printing products and experiencing increasing demand, yet still facing issues of waste and product defects , particularly in the press process. The number of defects reached 372 units from September to November. This study aims to design process improvements using a Lean manufacturing approach with Value Stream Mapping (VSM) , and waste identification using borda questionnaires, VALSAT, Process Activity Mapping (PAM), Supply Chain Response Matrix (SCRM), Quality Filter Mapping (QFM), fishbone diagram, and the 5Whys + 1How method . The VSM results show a lead time of 16,551.46 seconds and a cycle time of 16,138.02 seconds, with a significant proportion of non-value-added activities. The dominant waste types are defects and overprocessing. PAM analysis indicates the presence of delay and transportation, while SCRM reveals work-in-process accumulation as the main source of waiting. QFM identifies the press process as a critical point, with blurred fabric defects caused by unstable temperature, pressure, and material variation. The root cause lies in the absence of standardized process parameters and pre-heating procedures. The proposed improvement is the development of SOPs based on ISO 9001 to stabilize processes, reduce defects, and improve efficiency and quality consistency. Abstrak. CV Stadium Sport Banjarnegara adalah perusahaan manufaktur garmen yang memproduksi produk cetak jersey dan mengalami peningkatan permintaan, namun masih menghadapi masalah pemborosan dan cacat produk, khususnya pada proses press. Jumlah cacat mencapai 372 unit dari bulan September hingga November. Penelitian ini bertujuan untuk merancang perbaikan proses menggunakan pendekatan Lean Manufacturing dengan Value Stream Mapping (VSM), serta identifikasi pemborosan menggunakan kuesioner borda, VALSAT, Process Activity Mapping (PAM), Supply Chain Response Matrix (SCRM), Quality Filter Mapping (QFM), fishbone diagram, dan metode 5Why + 1How. Hasil VSM menunjukkan lead time sebesar 16.551,46 detik dan cycle time sebesar 16.138,02 detik, dengan proporsi aktivitas tidak bernilai tambah yang cukup signifikan. Jenis pemborosan yang dominan adalah cacat (defect) dan pemrosesan berlebih (overprocessing). Analisis PAM mengindikasikan adanya keterlambatan (delay) dan transportasi, sementara SCRM mengungkapkan penumpukan barang dalam proses (work-in-process) sebagai sumber utama waktu tunggu. QFM mengidentifikasi proses press sebagai titik kritis, dengan cacat kain buram yang disebabkan oleh suhu, tekanan, dan variasi material yang tidak stabil. Akar permasalahan terletak pada tidak adanya parameter proses yang terstandarisasi dan prosedur pemanasan awal (pre-heating). Usulan perbaikan yang diajukan adalah pengembangan SOP berbasis ISO 9001 untuk menstabilkan proses, mengurangi cacat, serta meningkatkan efisiensi dan konsistensi kualitas.